O sistema educacional equitativo e o background familiar: evidências para as microrregiões brasileiras em 2000 e 2010 - Santana, Fernanda Leite (2012)
The present dissertation aims to evaluate the supply of educational public services at basic education and high school on the Brazilian micro-regions between 2000 and 2010, as well as to investigate its relation with the intergenerational educational mobility. For this purpose, two complementary empirical strategies were applied to the school census data and to the demographic census. In the first one, by using the Data Envelopment Analysis, the Educational Coverage Index (ICE) will be estimated based on the Puig-Junoy (1999) approach, to identify regions with efficient educational coverage, as well as those with relative deficits. Through georeferencing, it appears that the level of educational coverage of high school showed up better than in elementary school. Furthermore, investigating the incomes of local scales, it appears that both educational strata in the majority of the analyzed micro-regions reached diminishing returns. In the second part, devoted to investigate whether a more favorable environment for investment in human capital afforded by a better education supply, can minimize the effects of intergenerational persistence, indicate at first, that this can reduce the influence of illiterate parents in the decision to invest in human capital as well as reduce educational inequalities in terms of country and region. Besides that, the obtained results from the econometric model developed by Ferreira and Veloso (2003) suggest that the improvement in the public supply tends to create opportunities while reducing the intergenerational persistence and thus provide an improvement in intergenerational educational mobility.